Influence of processing conditions on morphology of metal foams produced from metal powder - Körner, Carolin; Berger, F.; Arnold, Michael; Stadelmann, Claudia Gerda; Singer, Robert (Materials Science and Technology, 2000)
The influence of the processing conditions on the evolution of the cell morphology of aluminium foams is investigated. The precursor material, a compacted mixture of aluminium and titanium hydride powder, is foamed to different degrees by heating it to different maximum temperatures. The pressure of the surrounding argon atmosphere is varied from low pressure to overpressure. The cell morphology is characterised by the mean cell diameter, its circularity, and the gas/metal interface length per unit area. The cell morphology is found to be primarily determined by the density and cannot be influenced by the outside pressure. The morphology is governed by one simple evolution law: the mean cell wall thickness is constant during expansion. © 2000 IoM Communications Ltd.
UnivIS-Import:2015-03-09:Pub.2000.tech.IW.LWWTM.influe